ANALISIS KIMIA BEBERAPA JENIS KAYU DARI INDONESIA BAGIAN TIMUR (Chemical analysis of several wood species from East Indonesia) - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
This paper reported the result of chemical analysis of nine wood species from East Indonesia. The analysis comprise of the determination of holocellulose, cellulose, lignin, pentosan, ash content, silica content and the solubility in cold water, hot water, one percent of sodium hydroxide and alcohol benzene extractives. These analysis were conducted to determine their basic characteristics and ultimate uses of the wood. The result showed that holocellulose content ranges from 66,91 - 75,29 %, cellulose from 43,50- 54,72 %, lignin from 24,04 - 33,09 %, pentosanfrom 14,34 - 18,95 %, ash content from 0,38 - 2,13 %, silica content from 0,12 -1,91 %, The solubility in cold water rangesfrom 2, 71 - 8,42 %, hot water from 2,87 - 8,92 %, in NaOH 1 % from 12,34 - 26,65 % and in alcohol benzena (1:2) from 2,42-11,86 %. Based on chemical analysis, especially the cellulose content the 9 wood species from East Indonesian are suitable as raw material for pulp and paper industry.Keywords: IBT, Chemical Component.